Preliminary Assessment of Growth Performance and Nutrient utilization of Clarias gariepinus (Burchell, 1822) Fingerlings fed Cirina forda (Westwood, 1849) as Protein Source - Oso JA; Ola-Oladimeji FA (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
The potentials of Cirina forda as a replacement for fishmeal in the diets of Clarias gariepinus  fingerlings were evaluated in 56 days. Five diets namely diets A (100% fishmeal and 0%Cirina forda), B (75% fishmeal and 25% Cirina forda), C (50% fishmeal and 50% Cirina forda), D (25% fishmeal and 75% Cirina forda), and E (0% fishmeal and 100% Cirina forda) were compounded and given to the fingerlings at 5% body weight. Growth performance traits and nutrient compositions were measured, recorded and analysed. The highest final mean weight and mean weight gain were obtained in diet E containing 100% Cirina forda while the least values were recorded in diet C at 50% inclusion of Cirina forda. This indicates that Clarias gariepinus can tolerate 100% Cirina forda as a protein source without any inclusion of fishmeal. This will subsequently reduce the cost of feed production in the culture of Clarias gariepinus.